Bounding the resources for thermalizing many-body localized systems - Carlo Sparaciari (Nature Portfolio, 2021)
The thermalization of many-body localization phases poses a number of open questions related to our understanding of thermalization in quantum systems. Here, the authors aim to demonstrate that a quantum information approach can be used to investigate the mechanisms of thermalization in a quantum many-body system when coupled to an external system.